(untitled) (Conferencea, 2023)
Currently, the national education system is being modernized and the main directions of its reorganization are being established: ensuring the global competitiveness of education, its compliance with modern social and world trends, the upbringing of a harmonious and socially responsible person. In this regard, the model of the teacher is being modified as an expert on a high level of responsibility, competence, communication flexibility, socially significant values and moral standards of social consciousness.